Dike Complexes in the Eastern Part of the Kaakhem Magmatic Area (Eastern Tuva): Composition, Age, Geological Position - V. A. Yakovlev; I. V. Karmysheva; S. N. Rudnev; D. V. Semenova; D. S. Yudin (Геодинамика и тектонофизика, 2024)
This paper presents the results of isotope-geochronological and petrological studies of gabbroic and combined diorite-granite dikes located in the eastern part of the Kaakhem magmatic area. Both groups of dikes cut through diorite-tonalite-plagiogranite associations of different ages (489±5 and 476±4 Ma). Zircons from granitoid of mingling dikes have an age of 477±3 Ma (LA-ICP-MS). The age of the gabbroic dikes was determined by LA-ICP-MS (zircon) and Ar-Ar (amphibole) methods and is 454±10 and 450±6.3 Ma, respectively. Similar contents of major and trace elements in basic and intermediate rocks of dikes indicate their formation from a single source with subduction characteristics. The salic rocks of the combined dikes vary in composition and are close to the heterogeneous diorite-tonalite-plagiogranite-granite associations of the host rocks. The formation of dike complexes occurred at the collisional stage of development of the Kaakhem magmatic area and is associated with the development of local extension zones.